A Double-Edged Sword: The Effects of Cartoon Media on the Development of Children’s Eating Habits - Lou, Jerry; Fan, Frank (International Journal of Innovative Research in Medical Science, 2025)
The global childhood obesity epidemic has been a rising health concern over the past two decades. Obesity is associated with premature death, type 2 diabetes, and many other serious diseases and health conditions. Developing healthy eating habits early at a young age is a way to prevent diet-related diseases. Given the substantial increase in the prevalence of childhood obesity, various research studies have been conducted to treat this public health issue. Health campaigns worldwide have depended on multiple methods to reduce this crisis, including physical activity and diet-control programs, medicine, and surgery. Recent studies have found an additional promising and encouraging way to promote healthy eating among children: cartoons. Cartoons can affect cognitive development and encourage positive behaviors in children. Cartoons promoting a healthy diet can influence the food choices of children. However, cartoons have drawbacks as consuming media creates a sedentary lifestyle and could also be used to promote unhealthy foods to children. This review analyzes the effects of cartoons on children, how exposure to cartoon images can change children's behaviors and the underlying mechanisms of graphic media. Although using cartoon images is a promising way to reduce the prominence of childhood obesity, due to limited data concerning the long-term benefits of exposure to media, the combination of healthy eating cartoons with other traditional healthy eating techniques should also be considered.